Cytokine profile in autistic patients - Eftekharian, Mohammad Mahdi; Ghafouri-Fard, Soudeh; Noroozi, Rezvan; Omrani, Mir Davood; Arsang-jang, Shahram; Ganji, Maziar; Gharzi, Vajiheh; Noroozi, Hanieh; Komaki, Alireza; Mazdeh, Mehrdokht; Taheri, Mohammad (Cytokine (Philadelphia, Pa.), 2018)
The etiology of Autism Spectrum Disorders (ASDs) as severe neurodevelopmental ailments is not known. However, several evidences point to dysregulation of immune system as an underlying cause of ASD. In the present study we evaluated the mRNA expression levels of TNF-α, TGF-β, IFN-γ, CXCL8, IL-1β, IL-2, 1L-4, IL-6, IL-17 in whole blood samples of 30 ASD patients and 41 age and sex-matched healthy subjects with means of real-time PCR. TNF-α, IL-6 and IL-17 have been shown to be significantly up-regulated in ASD patients compared with healthy subjects (P < 0.0001, P = 0.001 and P < 0.0001 respectively). IL-2 has been shown to be significantly down-regulated in total ASD patients (P < 0.0001). No significant difference has been found in expression levels of other cytokines between patients and healthy subjects. The present study provides further evidences for dysregulation of immune response in ASD patients.